Correlation Analysis of Lactic Acid Level as A Predictor of Severity of Patients with Acute Appendicitis - Reno Rudiman; Tommy Ruchimat; Cytra Givanni Rossy (Majalah Kedokteran Bandung, 2023)
Perforated appendicitis is a leading cause of morbidity and mortality in all appendicitis cases, both for adults and children. Delay in preoperative diagnosis is the main reason for perforation. In previous studies, it was revealed that diagnostic modalities such as radiological examination and the current scoring system have not been able to predict the onset of perforated appendicitis. Serological biomarkers of lactic acid are associated with intestinal obstruction and ischemia. The increase in the serological value of lactic acid in perforated appendicitis compared to acute one was shown to increase significantly by 0.25 mmol/L (p<0.05) according to a previous study. This study aimed to determine the correlation between lactic acid level and the severity of appendicitis in patients visiting Dr. Hasan Sadikin General Hospital. This was a cross-sectional prospective analytic observational study on adult patients diagnosed with appendicitis who were admitted to the emergency room of Dr. Hasan Sadikin General Hospital from January 1, 2021 to June 1, 2021. Data analysis was performed using bivariate analysis and correlation tests of difference. This study involved 54 subjects with a mean lactic acid level of 2,5093 mmol/L (0.9 mmol/L - 11.8 mmol/L). In the complicated appendicitis group, 20 subjects (37%) was found to experience an increase in lactic acid (OR 1.07; 95% CI: -0.03-0.22; p=0.14). The correlation analysis showed the direction of negative correlation. Thus, it is concluded that there is no significant correlation between lactic acid level and the severity of appendicitis in patients with appendicitis.